Cyber Infidelity Evidence in Divorce Litigation: Reconstructing Judicial Reasoning in Indonesian Religious Courts - Novendri Eka Saputra; Ilham Ramadhani; Zalaria Abdiwali Mohamed (Legitima : Jurnal Hukum Keluarga Islam, 2026)
Purpose – This study examines judicial reasoning, disparities in the standard of proof, and the reconstruction of judicial reasoning regarding the proof of cyber infidelity in divorce cases in the Indonesian religious courts. The study stems from the lack of operational standards of proof regarding the use of digital communications as evidence of marital discord in the digital age. Methods – This study employs a normative legal methodology with a case-based approach, analyzing ten divorce rulings from the South Jakarta Religious Court in 2024 involving allegations of cyber infidelity through WhatsApp conversations, social media, and other forms of electronic communication. The analysis was conducted qualitatively, focusing on four indicators: admissibility, authentication, correlation of evidence, and substantive relevance of electronic evidence. Findings – The results of the study reveal three main findings. First, all rulings formally accepted electronic evidence but did not treat it as standalone or conclusive evidence. Second, the majority of rulings required corroboration through witness testimony, admissions by the parties, and narratives of domestic conflict to strengthen the probative value of digital communications. Third, none of the cases involved digital forensic examination; therefore, judges relied more on contextual and relational assessments in determining the reliability of electronic evidence. Consequently, cases with similar factual patterns resulted in different evidentiary assessments. This study argues that the primary issue in proving cyber infidelity does not lie in the admissibility of electronic evidence but rather in the absence of structured parameters for judicial reasoning when assessing the authentication and substantive relevance of digital evidence. Research implications/limitations – This study offers a reconstruction model that integrates the theory of judicial reasoning, assessment of digital evidence, theory of legal certainty, and principles of maqāṣid al-syarī‘ah. The model is designed to enhance the consistency of rulings, legal certainty, and substantive justice in contemporary Indonesia’s digital divorce cases.